2011
DOI: 10.1371/journal.pone.0017812
|View full text |Cite
|
Sign up to set email alerts
|

DNA Barcoding of Catfish: Species Authentication and Phylogenetic Assessment

Abstract: As the global market for fisheries and aquaculture products expands, mislabeling of these products has become a growing concern in the food safety arena. Molecular species identification techniques hold the potential for rapid, accurate assessment of proper labeling. Here we developed and evaluated DNA barcodes for use in differentiating United States domestic and imported catfish species. First, we sequenced 651 base-pair barcodes from the cytochrome oxidase I (COI) gene from individuals of 9 species (and an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0
6

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(55 citation statements)
references
References 27 publications
3
46
0
6
Order By: Relevance
“…This result likely reflects mislabelling in GenBank, as these two species are morphologically (and genetically) similar. A similar situation was previously documented for the two catfishes Clarias macrocephalus and C. batrachus (Wong et al, 2011). BOLD-IDS validates its identification search only if the species in the reference database has at least three barcoded specimens and identifies the query sequences if it matches the reference sequence within the conspecific distance of less than 1% (Ratnasingham and Hebert, 2007).…”
Section: Discussionsupporting
confidence: 64%
“…This result likely reflects mislabelling in GenBank, as these two species are morphologically (and genetically) similar. A similar situation was previously documented for the two catfishes Clarias macrocephalus and C. batrachus (Wong et al, 2011). BOLD-IDS validates its identification search only if the species in the reference database has at least three barcoded specimens and identifies the query sequences if it matches the reference sequence within the conspecific distance of less than 1% (Ratnasingham and Hebert, 2007).…”
Section: Discussionsupporting
confidence: 64%
“…GenBank Accession nos. JF292392-JF292380; Wong et al, 2011). Other Ictalurus species' entries showed a lower sequence similarity (<94%) for the same level of query coverage (i.e.…”
Section: Confirmation Of Ictalurus Punctatus Presence In Portugalmentioning
confidence: 97%
“…Many DNA barcoding researches has demonstrated that COI contains sufficient variation to accurately identify a large variety of animals, including both freshwater (Hubert et al 2008) and marine aquatic organisms ( Rock et al 2008;Spies, Gaichas, Stevenson, Orr, & Canino, 2006;Ward, Holmes, White, & Last, 2008;Ward, Zemlak, Innes, Last, & Hebert, 2005), to the species level (Waugh, 2007). Especially, COI gene barcoding has provided numerous successful examples demonstrating its reliability for the identification of fish, such as tuna (Lowenstein et al 2010;Terol, Mascarell, Fernandez-Pedrosa, & Perez-Alonso, 2002), flatfish (Espineira, Gonzalez-Lavin, Vieites, & Santaclara, 2008;Terol et al 2002), anchovy (Jerome et al 2008), and catfish (Wong et al 2011), as well as other economic aquatic species (Ardura, Linde, Moreira, & Garcia-Vazquez, 2010;Galal-Khallaf et al 2014). At present, the barcoding of common economic aquatic products has become increasingly important in the supervision of the market trade (Carvalho et al 2011).…”
Section: Introductionmentioning
confidence: 99%